How Did Educators of Students with Learning Differences Use Social–Emotional Learning to Support Their Students and Themselves Early in the COVID-19 Pandemic?. Issue 1 (8th December 2021) - Eveleigh, Abigail; Cook, Amanda; Naples, Lauren Hunter; Cipriano, Christina
Abstract: This study investigated the affective experiences of 30 educators of students with learning differences (sLD) and their use of social–emotional learning (SEL) early in the COVID-19 pandemic. Authors utilized a convergent parallel mixed-methods research design to collect and analyze data from educators through focus groups, interviews, and surveys. Through integrated analysis of qualitative and quantitative responses, authors found that educators of sLD experienced a range of emotions, both negative and positive, as they shifted to a virtual learning environment. Experiences of negative emotions were rooted in anxiety and stemmed from evolving demands and the increased challenges of adapting to distance learning, particularly for their sLD. Experiences of positive emotions stemmed from transformed relationships and new routes of communication with educators' colleagues, students, and families. Importantly, SEL strategy use for themselves and with their students served as a useful tool in navigating the challenges that the educators were facing. Findings are discussed in the context of how best to support educators who work with sLD and utilize SEL to manage the challenges of distance learning.